2007
DOI: 10.1086/513433
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes Stratified by Baseline Immunological Status among Young Children Receiving Nonnucleoside Reverse-Transcriptase Inhibitor-Based Antiretroviral Therapy in Resource-Limited Settings

Abstract: A study of 568 children aged <5 years who commenced nonnucleoside reverse-transcriptase inhibitor-based antiretroviral therapy in resource-limited settings revealed good early outcomes. After 12 months of antiretroviral therapy, survival probability was 0.89 (95% confidence interval, 0.86-0.92), with no significant difference among children stratified on the basis of baseline immunological levels; 62% attained a CD4 cell percentage >25%, and 7% continued to have a CD4 cell percentage <15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 8 publications
3
25
1
1
Order By: Relevance
“…[3][4][5][6][7] As a result, there have been clinically significant reductions in morbidity and mortality, converting the infection into a chronic condition in persons who receive HAART.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] As a result, there have been clinically significant reductions in morbidity and mortality, converting the infection into a chronic condition in persons who receive HAART.…”
mentioning
confidence: 99%
“…the overall increase in CD4% among all children in our study and stratified by baseline immunological status are comparable to those reported in pooled analyses of results from other pediatric cohorts in similar resourceconstrained settings. 28,29 We observed that children with severe immunosuppression (CD4% <15%) at baseline had more than 3 times the odds of failure to attain CD4% ≥25% at 12 months compared with those not severely immunosuppressed, and only half of these children attained CD4% values above 25% after 12 months of Art. these results emphasize the importance of early initiation of Art before severe immunosuppression.…”
Section: Discussionmentioning
confidence: 88%
“…Seventy-nine percent of the patients in this study had the baseline CD4 cell percentage Ͻ15%. 8 Seventy-three percent of our patients achieved viral suppression at week 48 of treatment. This is comparable with that of a Belgian cohort of 17 infants Յ2.5 months of age, where 71% achieved viral suppression at week 48.…”
mentioning
confidence: 72%
“…The petechial component of the acral lesions was not prominent, oral erosions were not present, and fever was absent. 8 Human parvovirus B19 (PVB19) infection was seen in 4% of the patients, 8 and blood irregularities rarely encountered. We report a case and review the literature, about the general characteristics of childhood and adolescent cases.…”
Section: Discussionmentioning
confidence: 99%